The Role of Physiotherapy in Children with Autism Spectrum Disorder: Case Report - Rachmatika, Bahertha; Naufal, Adnan Faris; Muazarroh, Salma (Prosiding University Research Colloquium, 2023)
Autism Spectrum Disorder (ASD) is a complex neurobiological developmental disorder that is diagnosed in childhood. Physiotherapy can play a role in helping reduce problems to minimize the occurrence of growth and development disorders. Helps prevent spasticity by releasing the Golgi Tendon Organ(GTO), as well as doing massage to relax and reduce pain. After 3 treatments, the results obtained were a decrease in T0:4 to T3:0 as measured using the Wong Baker FACES Pain Rating Scale. Spasticity decreased from T0:2 to T3:0 which was assessed using the Ashworth scale. The results showed that GTO release and massage were effective in ASD cases.